2020
DOI: 10.1007/s10898-020-00906-y
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between the extended supporting hyperplane algorithm and Kelley’s cutting plane algorithm

Abstract: Recently, Kronqvist et al. (J Global Optim 64(2):249–272, 2016) rediscovered the supporting hyperplane algorithm of Veinott (Oper Res 15(1):147–152, 1967) and demonstrated its computational benefits for solving convex mixed integer nonlinear programs. In this paper we derive the algorithm from a geometric point of view. This enables us to show that the supporting hyperplane algorithm is equivalent to Kelley’s cutting plane algorithm (J Soc Ind Appl Math 8(4):703–712, 1960) applied to a particular reformulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…In the last decades, solvers for convex MINLPs have demonstrated that the choice of the reference point in which to linearize convex nonlinear constraints is essential. While using the solution of the LP relaxation still leads to a convergent algorithm [54], better performance is achieved by using a reference point that is close to or at the boundary of the feasible region [26,97]. Therefore, also the new implementation of cons nonlinear includes a feature where feasible solutions are used as reference points to generate cutting planes.…”
Section: Linearization In Incumbentsmentioning
confidence: 99%
“…In the last decades, solvers for convex MINLPs have demonstrated that the choice of the reference point in which to linearize convex nonlinear constraints is essential. While using the solution of the LP relaxation still leads to a convergent algorithm [54], better performance is achieved by using a reference point that is close to or at the boundary of the feasible region [26,97]. Therefore, also the new implementation of cons nonlinear includes a feature where feasible solutions are used as reference points to generate cutting planes.…”
Section: Linearization In Incumbentsmentioning
confidence: 99%
“…In a recent paper of Serrano et al [22] it was shown that the supporting hyperplane algorithm [23] is equivalent to Kelley's cutting plane algorithm when reformulating the feasible region of the problem using its (sublinear) gauge function. This is theoretically interesting and in principle the case (neclecting the numerical differences) when comparing the smooth convex NLP algorithms of Kelley [6] and Veinott [24].…”
Section: Supporting Hyperplanes Standard Cutting Planes or Projected Cutting Planesmentioning
confidence: 99%